Effect of light-curing protocols on the mechanical behavior of bulk-fill resin composites - Besegato, João Felipe; Jussiani, Eduardo Inocente; Andrello, Avacir Casanova; Fernandes, Ricardo Vignoto; Salomão, Fabio Martins [UNESP]; Vicentin, Bruno Luiz Santana; Dezan-Garbelini, Cássia Cilene; Hoeppner, Márcio Grama (Elsevier, 2019)
Objective: To investigate the effect of two light-curing protocols on mechanical behavior of three bulk-fill resin composites (BFRC) considering their optical properties. Methods: One increment of 4 mm thickness of the bulk-fill resin composites Opus Bulk Fill, Tetric N-Ceram and Filtek Bulk Fill Flow were submitted to two different light-curing protocols: Sp - irradiance of 1000 mW/cm2 (20 s); Xp - irradiance of 3200 mW/cm2 (6 s). To assess the influence on the mechanical behavior it was studied polymerization shrinkage by X-ray microtomography (n = 3), Vickers hardness (n = 10) at the top and bottom surfaces of the samples, irradiance reaching the bottom surface (n = 3) and absorbance spectrum during the light-curing time interval (n = 3). Data were analyzed by two-way ANOVA test for parametric data and Kruskal Wallis test, followed by Wilcoxon or Mann-Whitney U post-test, for non-parametric data. Results: All BFRCs contracted when light-cured, with greater contraction for Xp. Filltek Bulk Fill Flow showed highest polymerization shrinkage, for both Sp and Xp. All BFRCs showed minor hardness values on the bottom surface, with greater reduction for Xp. All BFRCs exhibited a decrease in irradiance at 4 mm depth. A decrease in absorbance intensity throughout the light-cure was observed, except for Opus Bulk Fill. Conclusions: Regardless BFRCs composition, the light-curing protocol with lower irradiance and longer exposure time results in lower polymerization shrinkage and higher hardness. The higher irradiance in a shorter time interval compromises the mechanical behavior of the resin composites, which may result in undesirable clinical outcomes.
Keywords: Absorbance; Composite resins; Dental materials; Hardness; Irradiance; Physical properties; Polymerization; X-ray microtomography